'Culture of Religion' – a controversial secular school subject. Issue 1 (2nd January 2020) - Štimac, Zrinka
ABSTRACT: This paper analyses the context, emergence, organisation and curriculum of the school subject known as 'Culture of Religions' ( Kultura religija ), which is given as an example of good practice in the Toledo Guiding Principles of the OSCE. It was designed, piloted and to a certain extent introduced in state schools in Bosnia and Herzegovina by a collaboration of international organisations and institutions, together with representatives from various local organisations. This paper addresses the challenges and opportunities that render this school subject not only highly relevant but also a controversial issue of education policy today.